The Development of Lectora Inspire Learning Media and Its Effect on Student Learning Outcomes - Muhammad Rizki Harahap; Albinus Silalahi; Zainuddin Muchtar; Nurfajriani Nurfajriani (Journal of Educational Chemistry (JEC), 2022)
This study aimed to determine the needs of learning media in schools, the feasibility of the media created following the National Education Standards Agency (BSNP) criteria, and the effectiveness of the learning media on student learning outcomes. This research employed the ADDIE method (Analysis, Development, Design, Implementation, and Evaluation) involving 30 class X (tenth-grade) students. According to the analysis results of the Lectora Inspire media, the mean score of the content feasibility aspects was 3.88 (highly feasible), and the mean score of the presentation feasibility aspects was 3.89 (highly feasible). Furthermore, the developed media was implemented in the teaching and learning process to determine its effect on student learning outcomes. The test incorporated multiple-choice questions. In the implementation phase, the mean score of the pretest was 46.83, while the mean score of the posttest was 81.66. Afterward, the evaluation stage compared the posttest results and the school's passing grade (81.66 70), revealing that the developed learning media significantly affected student learning outcomes.